A nationwide cross-sectional study to analyse the impact of the COVID-19 pandemic on lifestyle and manifestations of polycystic ovarian syndrome among clinically diagnosed polycystic ovarian syndrome cases aged 15-49 years - Shah, Sneh M.; Mohanty, Sthitapragnya; Kaduluri, Chandana S.; Bhatt, Gneyaa S.; Ninama, Pallavi; Bapat, Nirav K. (International Journal Of Community Medicine And Public Health, 2022)
Background: Polycystic ovarian syndrome (PCOS), a gynecological and endocrine disorder closely linked with one’s lifestyle, has been impacted by the lockdowns imposed during the COVID-19 pandemic in India. Hence, our objective was to study the effect of the COVID-19 pandemic on the lifestyle and the manifestations of women with PCOS, and the association between them. Methods: Nationwide cross-sectional study was carried out among women diagnosed with PCOS via Rotterdam’s criteria using predesigned semi-structured questionnaires via social media. Data was analysed using proportions and Chi-square tests. Results: Majority females were between 20-29 years (78.3%) and obese (54.8%). Only 12 were physically active, with lack of motivation being the commonest reason for not exercising. 66.9% gained weight (average 6.62 kg). 72.6% noticed an increase in stress levels. 51.7% and 25.9% had severe and moderate anxiety respectively as per GAD (Generalized Anxiety Depression) score. Only 28.5% were satisfied with their sleep. 62.4% reported having irregular menstrual cycles, with an increase of 4.6% from before the pandemic. 39.2% women reported to have missed cycles often during the pandemic. 35.4% of women had an increase in hirsutism. A significant association was found between regularity of menses and one’s weight, physical activity and anxiety. Stress levels and sleep were found to be associated with change in the pattern of body hair. Conclusions: Overall compared to the pre-pandemic times, lifestyle deteriorated, with worsening of stress levels, physical activity, sleep and weight gain in spite of improvement in diet. Manifestations of PCOS showed exaggerated menstrual symptoms and increased hirsutism.